BUDAYA PERUSAHAAN BERBASIS KEARIFAN LOKAL DI PT. MUSTIKA RATU, TBK - Atmadi, Gayatri (Communication, 2013)
Competition in the business world today feels increasingly strengthened demandsevery company to always produce the best quality products. For the cosmetic company inIndonesia, the onslaught of import products from Japan, China, United Kingdom, France andthe United States are flooding the market need serious handling so that Indonesian canappreciate their products of their own nation. With the foundation of a corporate culture thatis rooted on the philosophy of Javanese culture, such as : toto, titi, titis, tatag, tetep, tanggap,teguh and trengginas, The leadership on PT. Mustika Ratu Tbk. was able to make and developa good corporate communication. Understanding corporate culture includes efforts toincrease customer satisfaction, working with family and cultural familiarity, respect forintegrity and professionalism is high as well as mutual support and cooperation in achievingthe corporate goal.Using the approach of qualitative and descriptive method, this study seeksto be an interesting article about understanding the implementation of corporate culturebased on the philosophies of Javanese culture. The collection of data obtained through thesource text, such as: books and articles from some of the media on line that is circulating inthe community.